THU0523 CLINICAL UTILITY OF TESTING CONVENTIONAL AND NON-CONVENTIONAL ANTI-PHOSPHOLIPID ANTIBODIES IN SUSPECTED OBSTETRIC ANTI-PHOSPHOLIPID SYNDROME. (2nd June 2020) - Ganapati, A.; K, J.; Nair, A.; Mathew, A.; Goel, R.; Mathew, J.; Prakash, J. A. J.; Nair, S. C.; Danda, D.
Abstract : Background: Anti-phospholipid syndrome (APS) is an important cause for recurrent pregnancy losses (RPL). Conventional APS antibodies (aPLs) like lupus anti-coagulant (LA), anti-cardiolipin(ACL) and anti-beta 2 glycoprotein I (anti-β2 GP I) are not present in significant number of obstetric APS(OAPS) patients, leading to a state described as " sero-negative" OAPS (SNOAPS). Recent literature shows non-conventional aPLs like Anti phosphatidylserine-prothrombin complex (Anti-PSPT) and Anti-Annexin V (Anti-Ann V) can be positive in up to 50% of SNOAPS patients Objectives: Testing the performance of conventional and non-conventional aPLs in suspected OAPS patients (obstetric events as defined in the Sydney classification criteria for APS) Methods: We performed a retrospective chart review of 101 patients who underwent combined testing for non-conventional aPLs for suspected OAPS from May 2016 to November 2019 at our department. Patients were categorized into OAPS cases (n=50, median age 31 years) and controls (n=51, median age 30 years) based on their fulfillment of clinical definition of OAPS events defined by Sydney criteria. Conventional aPLs were tested by methods adapted in Sydney criteria and Anti PSPT /Anti Ann V were tested by commercial ELISA. The sample size(n=101) has 95% confidence interval with a margin of error of 10% for the objective of the study. Results: 36 cases (72%) were 'sero-positive' & 14 cases (28%) were truly 'sero-negative' for conventional aPLs. 5 (35.7%) of the SNOAPS patients were positive for Ant-PSPT and/or Anti AnnV antibodies. Performance of the various aPLs in suspected OAPS is displayed in Table 1 & Figure 1 . Conclusion: In a delicate situation like RPL, performance of non-conventional aPLs on their own, though not as sensitive as conventional aPLs, still demonstrate better specificity. Non-conventional APLs can newly identify 1/3rd of SNOAPS as APS. The real value of testing Anti PSPT & Anti Ann V in RPL, is combined testing with conventional aPLs wherein they improve the sensitivity and accuracy of diagnosis of OAPS by 10% & 4.4 % respectively, with only 1.9% drop in specificity. Non-conventional aPLs should be tested in SNOAPS. Disclosure of Interests: None declared